Child Marriage in Kabang, South Yala, Thailand: Islamic Family Law Perspective - Aziz, Nasaiy; Sholihin, Riadhus; Samoh, Miss Nifatimah (El-Usrah: Jurnal Hukum Keluarga, 2023)
This research examines the impact of underage child marriage in Kabang, South Yala Region, Thailand. This is an empirical legal research method analyzed from the Islamic Law perspective. Interviews and document analysis were the methods of data collection used in the study, by which community leaders in Kabang, South Yala Region, Thailand who were involved in the marriage of underage children were interviewed. This research reveals that the factors causing the marriage of underage children in Kabang are: economic, pre-pregnant, educational, and environmental factors. Additionally, the study finds that marriages between minors will inevitably end in divorce, burden parents, and have a detrimental effect on one's health. Consequently, this study recommends that those immediately accountable for this case the village chief, the priest, the parents or guardians, the intellectuals in the community, and the youth—should always take precautions to protect themselves and refrain from marrying when underage. Islamic family law views underage marriage as incompatible with the goal of marriage, which is to establish a sakinah mawaddah wa rahmah (happy) family. Underage marriage has more negative effects than positive ones; it is bad for the individual, the family, and the community, and it can even destroy the nation-state and the entire country.